Diagnostic accuracy of haptoglobin within ovarian cyst fluid as a potential point‐of‐care test for epithelial ovarian cancer: an observational study. (4th September 2017) - Mahyuddin, AP; Liu, L; Zhao, C; Kothandaraman, N; Salto‐Tellez, M; Pang, BNK; Lim, DGS; Annalamai, L; Chan, JKY; Lim, TYK; Biswas, A; Rice, G; et al.
Abstract : Objective: To investigate haptoglobin within ovarian cyst fluid (OCF) as a diagnostic biomarker for epithelial ovarian cancer (EOC) and develop an in vitro diagnostic point‐of‐care device test (IVDPCT) for use in the operating theatre. Design: Retrospective and prospective cohort study. Setting: South‐East Asia. Population: Women with suspicious ovarian cysts. Methods: Proteomic, immunohistochemical and ELISA methods measured haptoglobin in OCF to differentiate benign and EOCs. Diagnostic performance of haptoglobin was compared with CA125, risk malignancy indices (RMI) and frozen section. Blinded validation of the IVDPCT was performed. Main outcome measures: Prediction of malignancy. Results: Haptoglobin concentration measured by ELISA was 0.70 ± 0.09 mg/ml in patients with benign cysts ( n = 87), 6.22 ± 0.53 mg/ml in early stage‐EOC ( n = 17), and 6.57 ± 0.65 mg/ml in late stage‐EOC ( n = 20). Haptoglobin in EOCs was significantly higher than in benign cysts (P < 0.0001). Haptoglobin using rapid colorimetric assay (RCA) on a training set had a sensitivity of 97.3% and a specificity 92.0%, comparable to ELISA and frozen sections. The haptoglobin AUROC curve was 0.999 (95% CI 0.997–1.000) compared with 0.895 (95% CI 0.814–0.977, P < 0.05) for CA125. Haptoglobin performed significantly better than all the RMIs ( P < 0.01). Blinded validation studies showed a minor drop in average diagnostic performance (sensitivity 85.2% and specificity 90.5%) compared with the training set. However, when compared with frozen section, haptoglobin was no worse in diagnostic accuracy for malignancy. Conclusion: Haptoglobin was identified as a biomarker for the detection of EOC with potential as a point‐of‐care diagnostic tool. Tweetable abstract: Haptoglobin within ovarian cyst fluid: a biomarker for epithelial ovarian cancer and point‐of‐care diagnostics. Tweetable abstract: Haptoglobin within ovarian cyst fluid: a biomarker for epithelial ovarian cancer and point‐of‐care diagnostics.